246. Analysis of signal-to-noise ratio for a 2-channels coil developed to enable transcranial Magnetic Resonance-guided Focused Ultrasound Surgery (tcMRgFUS) with 1.5 T MRI scanners. (December 2018) - Marrale, M.; Collura, G.; Napoli, A.; Geraci, L.; Catalano, C.; Midiri, M.; Lagalla, R.; Gagliardo, C.
Abstract: Purpose: In recent years trans-cranial Magnetic Resonance-guided Focused Ultrasound Surgery (tcMRgFUS) treatments have aroused large scientific and medical interest[1] . Usually, tcMRgFUS systems are integrated with 3 T systems which allow the use of the body RF coil for both real time imaging and MR-thermometry. At University Hospital of Palermo there is the world-first installation of a tcMRgFUS system integrated with a 1.5 T scanner. Here we present the characterization in terms of signal-to-noise ratio (SNR) of a dedicated RF coils suitably developed (by InSightec) to enable tcMRgFUS treatments with 1.5 T MR units. Methods and materials: The focused ultrasound equipment (ExAblate 4000, InSightec) integrates with an MRI unit operating at 1.5 T (Signa HDxt, GE) and consists of a hemispheric 1024-element phased-array transducer. T2w-FRFSE images were obtained from a dedicated Dose Quality Assurance phantom using the same MRI protocol used for real treatments. Results: The dedicated flexible coil resulted in larger SNR values with respect to that achieved using MRI's body RF coil. In particular, we obtained for the axial plane a SNR equal to 27.5 using dedicated coil whereas it was equal to 2.5 with RF body coil (SNR gain more than 10 times higher). Conclusion: We can conclude that, even though the SNR linearly increases with magnetic field strength, the use of a dedicated coil on a 1.5 T scanner enabled us to obtain images with a SNR roughly 5 times larger than those acquired on 3T scanners using MRI's body RF coil. This could facilitate the spread of this cutting-edge technology worldwide[2] .